Self-control and child abuse potential in mothers with an abuse history and their preschool children - Henschel, Saskia; de Bruin, Marijn; Möhler, Eva (Journal of child and family studies, 2014)
We examined whether physically and sexually abused mothers display lower levels of self-control, whether this explains their higher tendency to abuse their own children, and if this results in lower levels of self-control among their children. In a cross-sectional study, 40 abused and 47 matched, non-abused mothers completed validated self-control and child abuse potential questionnaires. Their preschool children (2.3-3.7 years) were tested for self-control with the effortful control battery and delay of gratification test. Relationships and mediations were tested using stepwise regression analyses and bootstrap mediation tests, while controlling for potential confounders. Mothers with a history of abuse had a significantly higher potential to abuse their children (p < .001) and lower levels of self-control (p < .05) compared to non-abused mothers. Maternal self-control predicted child abuse potential (p < .001) while controlling for maternal history of abuse, revealing that self-control partially mediated the relation between past abuse and current abuse potential. Next, child abuse potential was found to be a borderline significant predictor of child self-control (p = .05) on the delay of gratification task but not on the effortful control battery. We did not discover a correlation between child self-control and maternal self-control. These findings suggest that self-control may be a potentially important mechanism in the intergenerational cycle of child abuse. Further investigation on the topic is needed to confirm this hypothesis, for example through investigating the impact of parental self-control training on abusive parenting and children’s self-control development. Improved child self-control measures or focusing on older children is expected to address the key limitations of the current study.
Published online: 7 March 2013
Gesehen am 23.07.2020